If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -8 = 3y + -10 Reorder the terms: -8 + 2y = 3y + -10 Reorder the terms: -8 + 2y = -10 + 3y Solving -8 + 2y = -10 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -8 + 2y + -3y = -10 + 3y + -3y Combine like terms: 2y + -3y = -1y -8 + -1y = -10 + 3y + -3y Combine like terms: 3y + -3y = 0 -8 + -1y = -10 + 0 -8 + -1y = -10 Add '8' to each side of the equation. -8 + 8 + -1y = -10 + 8 Combine like terms: -8 + 8 = 0 0 + -1y = -10 + 8 -1y = -10 + 8 Combine like terms: -10 + 8 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| 3(x-3)+2x-3=4x-8 | | 5x+4=8x-30 | | -2-42=4x+33 | | 15x*6=12 | | 62(30x-80)-43(52-20x)=377 | | -2k=1/4 | | x-14=5x+18 | | 4732-500=x | | 12x+5=11(x+7)+10 | | 7x-1=x-1+6x | | 2m-6=-1+m-4m | | 4(2x+10)=16 | | -1/2(3x-5)=7 | | -t^3-6t^2+12t+50=0 | | 5(x-5)-12=23x-127 | | x^2-2x+8=-12+7x | | 9h=-39 | | 3x+5=90 | | 15=4*3.14*r | | 24x^2-4x-8= | | 4(6x+18)=120 | | 24x^2+4x-8= | | 10x+1=x-8+6x | | 6(x-7)-12=20x-222 | | 3.3d-7.2=0.8d+7.3 | | (12)-24=x | | 6(x-4)=6(x-1) | | 15=4(3.14)r | | 12*-24= | | 5n-5=-6n-16 | | a/15+4/15=9/5 | | 5(x-4)+4x=9x-20 |